A construção de cúpulas imaginárias na capitania de Minas Gerais : a pintura de perspectiva e a expressão de uma concepção religiosa - 1725 a 1800 - Luciana Braga Giovannini (2022)
The present PhD work corresponds to the study of a group of illusionistic perspective paintings which embellish the main chapels of five temples, located in three counties of the capitania of Minas Gerais, Vila Rica, Serro Frio and Rio das Mortes. Such ornamentations simulate circular centralized architectures, called Imaginary Domes. These are: the decorations of the ceiling of the main chapels of the Cathedral of Mariana (1760), the church of Santa Efigênia de Ouro Preto (c. 1765), both executed by the Portuguese painter Manoel Rabelo de Souza; the mother church of Santo Antônio de Ouro Branco (1760-1775), whose authorship is unknown; the mother church of Santana de Inhaí (before 1787), attributed to the Bracarense craftsman José Soares de Araújo; and the church of Nossa Senhora do Rosário dos Homens Pretos de Tiradentes (1760-1775), whose author we call Mestre do Rosário. Through a stylistic-formal analysis of the art works, we seek to investigate the interlocution between the quadraturistic practice developed in Minas Gerais and the North of Portugal, namely the provinces of Entre-Douro-e-Minho and Trás-os-Montes, regions whence most of the painters arrived in the auriferous and diamondiferous territory during the 18th century. To understand the message transmitted by the painting, we executed an iconographical analysis and, from its interpretation, we sought to correlate its content to the artistic and religious universe of the capitania of Minas Gerais, manifested by the cult of saints, the proclamation of sermons and religious festivities, whose production was based on a wide decorative apparatus, characterized by a close relationship between the faithful and the saints of their devotion. Since the beginning o four investigation, we observed that the artists who worked in Minas Gerais throughout the 18th century (and most of the painters who were active in the old provinces of Entre-Douro-e-Minho and Trás-os-Montes) did not create environments which break with the materiality of the ceiling of the mentioned churches, extending the real architecture, conducting the gaze of the observer into the infinite and triggering the emotion of wonder and religious ecstasy. During our investigation, we realized that the painted domes evoke the need for the construction of a centralized space composed by a central point, which determinates the place to be occupied by the observer. However, the composition of the paintings prioritizes the reproduction of figurative groups: the hagiographic and religious narratives. Thus, we defend the proposition that the artists, attending to the plans of their patrons, painted imaginary domes with the intention to express a religious conception. The dome represents the reconciliation between God and man, and the characters indicate the way the faithful must follow through in order to spiritually ascend and reach the Glory of God. In the studied pictorial set, quadrature must be understood in its symbolic dimension. From this point of view, we consider perspective painting to be more representative and emblematic than properly illusionistic. In this ambit, false architecture possesses a transitory character, in the sense that corresponds to the intermediary space between the earthly universe and the celestial realm.